The Influence of Social Capital, Entrepreneurial Competence, and Financial Inclusion on the Performance of UMKM in East Jakarta - Della Pariska; Ash Shoffi Hana Fadhilah; Sunarta; Irsyad Ali Amin (www.amertainstitute.com, 2025)
This study aims to investigate the relationship between MSMEs' social capital, financial inclusion, and entrepreneurial skill performance in East Jakarta. MSMEs play a significant part in economic expansion, but still face various challenges, especially in terms of access to social networks, entrepreneurial skills, and utilization of financial services. This study employs a survey method in conjunction with a quantitative approach through questionnaires distributed to 234 MSME players in East Jakarta. The SEM-PLS 3.0 technique was used to measure the association between variables in the data. The findings demonstrated that financial inclusion, entrepreneurial skill, and social capital all had a major positive impact on MSME performance. The findings confirm that strengthening social capital can improve access to information and business collaboration, while improving entrepreneurial competencies contributes to business innovation and more effective business management. In addition, greater financial inclusion assists MSMEs in gaining access to capital and financial services that support business sustainability. Therefore, policies and programs that promote the development of MSMEs through improved social networks, entrepreneurship training, and access to more inclusive financial services are needed.